2020
DOI: 10.3847/1538-4357/aba8f1
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Interstellar Sulfur Isotopes: A Radial 32S/34S Gradient?

Abstract: We present observations of 12C32S, 12C34S, 13C32S, and 12C33S J = 2−1 lines toward a large sample of massive star-forming regions by using the Arizona Radio Observatory 12 m telescope and the IRAM 30 m. Taking new measurements of the carbon 12C/13C ratio, the 32S/34S isotope ratio was determined from the integrated 13C32S/12C34S line intensity ratios for our sample. Our analysis shows a 32S/34S gradient from the inner Galaxy out to a galactocentric distance of 12 kpc. An unweighted least-squares fit to our dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…These are only slightly lower than the value of 22 in the Solar System. There is an obvious and confirmed 32 S/ 34 S gradient (Chin et al 1996;Yu et al 2020) from the inner Galaxy out to a galactocentric distance of 12.0 kpc. Nevertheless, there is a lack of data at small and large galactocentric distances.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…These are only slightly lower than the value of 22 in the Solar System. There is an obvious and confirmed 32 S/ 34 S gradient (Chin et al 1996;Yu et al 2020) from the inner Galaxy out to a galactocentric distance of 12.0 kpc. Nevertheless, there is a lack of data at small and large galactocentric distances.…”
Section: Introductionmentioning
confidence: 95%
“…To enlarge this sample, we chose 92 sources from the Bar and Spiral Structure Legacy (BeSSeL) Survey 1 in 2020. These 92 targets were recently released by the BeSSeL project (Reid et al 2019) and not observed by Yu et al (2020). In total, 110 objects in the Galaxy are part of our survey.…”
Section: Sample Selection and Distancementioning
confidence: 99%
See 2 more Smart Citations
“…where η BD is the beam-filling factor and θ s and θ beam are the source size and the HPBW, respectively (Zhang et al 2017;Yu et al 2020). According to T mb values measured by IRAM 30 m and ARO 12 m, the source size (HC 3 N J = 10−9) is estimated for those 33 sources except G010.32−00.15 and G109.87 +02.11 (unreasonable results of size, larger than the HPBW of ARO 12 m, may be nonuniform with a clumpy structure).…”
Section: Line Widthmentioning
confidence: 99%